Income Analysis of Coffee Farmers and Its Impact on Regional Development (Case Study: Pematang Sidamanik District, Simalungun Regency, Indonesia): English - Gulo, Tiurma; Lubis, Satia Negara; Lubis, Arga Abdi Rafiud Darajat (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
This study investigates the influence of government policies, supporting infrastructure, and farmer institutions on the income of coffee farmers in Pematang Sidamanik District, Simalungun Regency. Utilizing survey methods and data analysis, information was gathered from coffee farmers through interviews and questionnaires. The findings reveal that supporting infrastructure and farmer institutions significantly impact coffee farmers' income both collectively and individually. Conversely, government policies did not show a significant effect. Enhancing coffee production can positively contribute to regional development if backed by supportive policies. Recommendations include a committed governmental focus on priority development programs, particularly in agricultural infrastructure, strengthening farmer institutions, and increasing farmers' knowledge of technology and information. Implementing these recommendations is expected to facilitate more effective coffee agricultural development in Pematang Sidamanik District, improve farmers' welfare, and positively impact regional development as a whole.